ADOLESCENTS’ AWARENESS OF VARIOUS WAYS OF HUMAN TRAFFICKING AND PREVENTIVE STRATEGIES AS EXPRESSED BY SECONDARY SCHOOL STUDENTS IN OYO METROPOLIS - Shittu, John Idowu; Oyediran , Ayotunde Oyedele; Olukayode, Oyelade Oyekola (Sokoto Educational Review, 2015)
This study investigated adolescents’ awareness of the various ways of human trafficking and preventive strategies among secondary school students in Oyo metropolis. Two research questions and two hypotheses were raised to guide the study. Descriptive survey method was adopted to carry out the study. Stratified random sampling technique was employed to select 250 respondents for the study. A researcher designed questionnaire titled ‘Knowledge of Human Trafficking and Preventive Strategies Questionnaire’ (KOHTPSQ); was used as instrument for data collection. The research questions were answered using mean, while the research hypotheses were tested using the z-test statistics at 0.05 level of confidence. The findings showed that male and female students of secondary schools in Oyo metropolis are to a great extent, aware of the ways by which human can be trafficked. A significant difference existed in the knowledge of the ways by which human are being trafficked. It was recommended that counsellors should organise group counselling session/workshop/seminar/ conferences for adolescents’ and parents to educate them on various ways human can be trafficked. Also, government should intensify effort on preventive strategies against human trafficking.